Escherichia coli under Ionic Silver Stress: An Integrative Approach to Explore Transcriptional, Physiological and Biochemical Responses - Saulou-Bérion, Claire; Gonzalez, Ignacio; Enjalbert, Brice; Audinot, Jean-Nicolas; Fourquaux, Isabelle; Jamme, Frédéric; Cocaign-Bousquet, Muriel; Mercier-Bonin, Muriel; Girbal, Laurence (PLOS ONE, 2015)
For a better understanding of the systemic effect of sub-lethal micromolar concentrations of ionic silver on Escherichia coli, we performed a multi-level characterization of cells under Ag+-mediated stress using an integrative biology approach combining physiological, biochemical and transcriptomic data. Physiological parameters, namely bacterial growth and survival after Ag+ exposure, were first quantified and related to the accumulation of intracellular silver, probed for the first time by nano secondary ion mass spectroscopy at sub-micrometer lateral resolution. Modifications in E. coli biochemical composition were evaluated under Ag+-mediated stress by in situ synchrotron Fourier-transform infrared microspectroscopy and a comprehensive transcriptome response was also determined. Using multivariate statistics, correlations between the physiological parameters, the extracellular concentration of AgNO3 and the intracellular silver content, gene expression profiles and micro-spectroscopic data were investigated. We identified Ag+-dependent regulation of gene expression required for growth (e.g. transporter genes, transcriptional regulators, ribosomal proteins), for ionic silver transport and detoxification (e.g. copA, cueO, mgtA, nhaR) and for coping with various types of stress (dnaK, pspA, metA,R, oxidoreductase genes). The silver-induced shortening of the acyl chain of fatty acids, mostly encountered in cell membrane, was highlighted by microspectroscopy and correlated with the down-regulated expression of genes involved in fatty acid transport (fadL) and synthesis/modification of lipid A (lpxA and arnA). The increase in the disordered secondary structure of proteins in the presence of Ag+ was assessed through the conformational shift shown for amides I and II, and further correlated with the up-regulated expression of peptidase (hfq) and chaperone (dnaJ), and regulation of transpeptidase expression (ycfS and ycbB). Interestingly, as these transpeptidases act on the structural integrity of the cell wall, regulation of their expression may explain the morphological damage reported under Ag+-mediated stress. This result clearly demonstrates that the cell membrane is a key target of ionic silver.